Needs Analysis of the Development Cooperative Project-Based Learning Models in the Digital Age: Analisis Kebutuhan Pengembangan Model Cooperative Project Based Learning di Era Digital - febriyanno Suryana; Abna Hidayati (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2020)
This study aims to Analyze the learning process in programming language courses to get information about the needs of lecturers and students as well as expectations in pedagogical learning. Analyze the need to develop project-based learning models and cooperative-based learning. The research method used was a survey method. Data were collected using questionnaires, interviews and observations. The research sample is S1 Information Systems Study Program students and Lecturers at the Computer Science Faculty of Putra Indonesia University ‘YPTK